2019
DOI: 10.1371/journal.pgen.1008097
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 directly regulates an autophagy network to functionally regulate proteostasis in adult neural stem cells

Abstract: Maintenance of a healthy proteome is essential for cellular homeostasis and loss of proteostasis is associated with tissue dysfunction and neurodegenerative disease. The mechanisms that support proteostasis in healthy cells and how they become defective during aging or in disease states are not fully understood. Here, we investigate the transcriptional programs that are essential for neural stem and progenitor cell (NSPC) function and uncover a program of autophagy genes under the control of the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 44 publications
(61 reference statements)
1
95
0
Order By: Relevance
“…All these factors induce the expression of LC3 [Polager et al., ; Settembre et al., ; Sanchez et al., ] whereas BNIP3 is overexpressed by both E2F1 and FOXO3a [Mammucari et al., ; Shaw and Kirshenbaum, ; Yurkova et al., ] and Beclin‐1 only by FOXO3a [Sanchez et al., ]. Very recent data also show that FOXO3 controls many autophagy genes in adult neural stem cells [Audesse et al., ]. In addition, we already know that Env triggers the production of ROS [Molina et al., ] and numerous data demonstrate that FOXO3a is activated in response to oxidative stress [Storz, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors induce the expression of LC3 [Polager et al., ; Settembre et al., ; Sanchez et al., ] whereas BNIP3 is overexpressed by both E2F1 and FOXO3a [Mammucari et al., ; Shaw and Kirshenbaum, ; Yurkova et al., ] and Beclin‐1 only by FOXO3a [Sanchez et al., ]. Very recent data also show that FOXO3 controls many autophagy genes in adult neural stem cells [Audesse et al., ]. In addition, we already know that Env triggers the production of ROS [Molina et al., ] and numerous data demonstrate that FOXO3a is activated in response to oxidative stress [Storz, ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is regulated by several transcription factors, including the forkhead transcription factor FOXO3a [Warr et al., ]. Many autophagy genes are under the control of FOXO3, including MAPLC3B (microtubule‐associated protein light chain 3B, hereafter referred to as LC3), ATG9A, ATG4B, ATG5, ATG10, Beclin 1, BNIP3 and ULK1 (Unc‐51 like autophagy activating kinase 1), depending on the cell type studied [Mammucari et al., ; Sanchez et al., ; Fullgrabe et al., ; Li et al., ; Audesse et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to hematopoietic stem cells, transcriptional regulation of the autophagy program in neural stem cells is mediated by the transcription factor FOXO3. In Foxo3-deficient neural stem cells, defective autophagy results in the accumulation of protein aggregates (Audesse et al, 2019). Interestingly, another study found that lysosome-associated genes are highly upregulated in quiescent neural stem cells in contrast to activated neural stem cells that express high levels of proteasome-associated genes (Leeman et al, 2018).…”
Section: Neural Stem Cellsmentioning
confidence: 99%
“…Another major mechanism of autophagy regulation is transcriptional and mediated by master transcriptional regulators that activate expression of the core ATGs. These include the transcription factor EB (TFEB; Palmieri et al, 2011;Settembre et al, 2011), microphthalmia-associated transcription factor (Ploper et al, 2015;Perera et al, 2015), and the forkhead family of transcription factors (FOXO1 and FOXO3;Audesse et al, 2019;Zhao et al, 2007;Mammucari et al, 2007;Sengupta et al, 2009). Recently, the epigenetic regulator bromodomain-containing protein 4 was identified as a transcriptional repressor of autophagy and lysosomal genes (Sakamaki et al, 2017).…”
Section: Macro-autophagymentioning
confidence: 99%